Modified peakedness in M/G/∞ queue busy cycle distribution - Ferreira, M. A. M. (Acta Scientiae et Intellectus, 2020)
We expose how a parameter, then called 0, analogous to the parameter n proposed in [1] to characterize the M/G/∞ queue busy period distribution, is also worthwhile to characterize the M/G/∞ queue busy cycle distribution. The parameters 0 and n are both modifications of the peakedness proposed in [3].